A Study on Corporate Criminal Liability: Comparative Approach (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Corporate criminal liability has become a pivotal subject in the realm of legal studies and governance due to the increasing complexity of corporate operations and the globalized nature of business. This article examines the evolution, theoretical underpinnings, and enforcement mechanisms of corporate criminal liability from a comparative perspective. The article elucidates the many methods of holding businesses liable for illegal actions by examining legal frameworks across nations, including civil law and common law systems. It also explores challenges related to mens rea, vicarious liability, and the role of compliance programs. Through a comparative lens, the article highlights emerging trends, such as corporate social responsibility (CSR) as a preventive measure and the impact of international conventions. The study concludes by recommending a harmonized approach to corporate criminal liability to enhance accountability and deterrence while fostering ethical corporate behavior globally.